Proposed framework for Tahkim in the construction industry - Arifin, Muhammad Arifuddin; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah (American Scientific Publishers, 2015)
Conventionally, arbitration is deemed the most frequently used alternative dispute resolution (ADR mechanism for settling construction related disputes. In Islam a similar approach in ADR, and is Shari’ah-compliant, is known as Tahkīm. While the practice and procedures in arbitration are well established but not much is known about Tahkīm. In line with the interest of the business community to seek ways to adopt Shari’ah-compliant practice and procedures it is considered important and urgent for the use of Tahkīm in settling construction related disputes to be promoted. This paper reports on a study to develop a proposed framework for Tahkīm. Methodology adopted for the study combines review of literature and interviews with Shari’ah, legal and construction experts. It concludes with a recommendation for the framework to be considered for use in settling construction related disputes.